Efetividade de um corredor ecológico à manutenção da diversidade bentônica em ecossistemas aquáticos lóticos - Pandolfo, Alana (2014)
The presence of riparian vegetation is unquestionable for the water quality of streams and rivers, because it buffers impacts coming from the surroundings of these ecosystems, particularly in areas used for agricultural and livestock activities. In this sense, this study aimed to evaluate and compare the composition and structure of the benthic invertebrate community in two first order streams, one located in an ecological corridor and another in continuous vegetation, but not set up as a corridor. We assumed that the riparian vegetation is the main factor influencing the water quality of these environments, especially the one inside the ecological corridor. To test our hypothesis, bimonthly sediment samples were taken with kick sampling for community analysis in three regions (headwaters, middle and mouth) of each stream. Samples were subjected to subsampling technique and invertebrates were identified to genus levels. The distribution and composition of taxa were similar between the two streams, with the exception of the headwaters of Apepu. In this sampling site, the sediment type and the successional stage of the riparian vegetation were not conducive to the integrity of the benthic community. However, community reestablishment was observed along the longitudinal axis of the stream according to the characteristics of natural environments and the presence of sensitive organisms. Furthermore, the similarity in biotic and abiotic composition of both streams highlight the importance of creating one more ecological corridor in the riparian vegetation of the Gualberto Stream, covering its watershed. These actions seek to preserve and maintain the biological diversity of water resources and ensure that measures aimed at water resource management are implemented and enforced as provided for in environmental legislation.